The Patient Griselda Myth : Looking at Late Medieval and Early Modern European Literature - Rüegg, Madeline (Berlin/Boston De Gruyter, 2019)
The Patient Griselda myth tells the story of a marquis who is reluctant to get married, but, under pressure from his subjects, agrees to take a wife and chooses a poor young country girl for her virtues. Once married, he doubts his wife s per-fection and therefore tests her for more than ten years by taking away her chil-dren, pretending to have them killed, and by repudiating her. Finally, the marquis asks her to prepare his second wedding with a young noble lady. This second wedding never occurs, since the marquis finally reveals that the bride and her brother are Griselda s children; what is actually celebrated is the family reunion and Griselda s patience. This tale, which to our modern perceptions may appear horrible, fascinated Europe from the late fourteenth century until the nineteenth century, as the many translations and adaptations it underwent attes
English
Keywords: Literature & literary studies; late Medieval; Early Modern Europe; literature